Design of porous Ni and rare earth metal (Ce, Ho, and Eu) Co-doped TiO2 nanoarchitectures for energy conversion and storage applications. (27th January 2023) - Bashir, Amna; Inayat, Abid; Bashir, Rabia; Jamil, Sadaf; Abbas, Syed Mustansar; Sultan, Muhammad; Iqbal, Azhar; Akhter, Zareen
Abstract : Herein, we have synthesized co-doped TiO2 nanoparticles. The synthesized nanoparticles were applied as potential candidates for water splitting and supercapacitor applications. Abstract : In the current work, TiO2 nanoarchitectures with high surface area and charge density have been synthesized by a facile hydrothermal method and further modified via co-doping with a transition metal (nickel) and rare-earth metals (europium, cerium, and holmium). Different characterization tools ( i.e., XRD, BET surface area, FTIR, Raman, PL, SEM, TEM, XAS, XPS, and DRS) have been used to check the effect of co-doping on the electrical, morphological, and structural properties of the TiO2 nanoarchitectures. The FTIR, Raman, and XRD results confirmed the successful co-doping of the TiO2 nanoarchitectures. The high surface area of the co-doped nanoarchitectures as compared to undoped and singly doped TiO2 was confirmed from BET measurements. The presence of dopants in various oxidation states was further elucidated via XPS and XAS studies. FE-SEM and TEM revealed the formation of interconnected, mesoporous-type nanoarchitectures, with particle sizes less than 100 nm. The supercapacitive behavior of synthesized nanoarchitectures was evaluated by performing cyclic voltammetry, linear scan voltammetry, galvanostatic charge–discharge, and electrochemical impedance measurements. The specific capacitance values ( C sp ) indicate that the co-doping of rare-earth metals into the TiO2 structure results in enhanced capacitance of the target materials. The highest capacitive behavior was observed in the Ni-Ho-3 sample (740 F g −1 ), followed by Ni-Eu-3 (630 F g −1 ), Ni-Ce-3 (552 F g −1 ), and Ni-5 (545 F g −1 ), as compared to that of pure TiO2 (240 F g −1 ). Furthermore, the Ni-Ho-3 electrode also showed better cyclic stability with 97% capacity retention after 1000 cycles at a high current density of 5 A g −1 . The water oxidation studies also showed that all the doped TiO2 nano-catalysts show enhanced oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) activity. The OER overpotential values at 10 mA cm −2 for Ni-Eu-3, Ni-5, Ni-Ce-3, and Ni-Ho-3 are 520, 550, 600, and 620 mV, respectively. The Tafel slopes of undoped TiO2, Ni-5, Ni-Eu-3, Ni-Ce-3, and Ni-Ho-3 are measured to be 151, 143, 134, 141, and 137 mV dec −1, respectively. The smallest Tafel slope of Ni-Eu-3 indicated its highest OER efficiency among all the selected samples. As compared with the other samples, Ni-Ho-3 sample also showed a lower value for the Tafel slope. The superior performance of co-doped nanoarchitectures was credited to the development of mesoporous structures with more electroactive sites, high charge density, and better charge transfer (EIS results).